Effects of body weight support training on balance and walking function in stroke patients: a systematic review and meta-analysis - Jiang, Zhaoxiang; Zhang, Xinxin; Fu, Qian; Tao, Yimin (Frontiers in Neurology, 2024)
Here is the revised passage with a reduction of 30 words: To evaluate the impact of body weight support training (BWST) on balance and gait in stroke patients based on evidence and identify the most effective intervention strategies, we searched PubMed, Web of Science, The Cochrane Library, CNKI, Wanfang, and Chinese SinoMed Database until November 25, 2023. Quality assessment and meta-analysis were conducted using RevMan 5.2 and Stata 14.0 software. We included 31 randomized controlled trials with 1,918 patients. The meta-analysis showed BWST significantly improved Berg Balance Scale (BBS) scores (MD=3.60; 95% CI: 1.23 to 5.98; p=0.003), gait speed (SMD=0.77; 95% CI: 0.38 to 1.15; p<0.0001), and step length (SMD=0.46; 95% CI: 0.19 to 0.72; p=0.0008) compared to conventional rehabilitation. For balance function, the most effective interventions were a disease duration of 3-6 months (MD=5.16; 95% CI: 0.76 to 9.57; p=0.02), an intervention time of 4-8 weeks (MD=5.70; 95% CI: 2.90 to 8.50; p<0.0001), a maximum body weight support level above 30% (MD=3.80; 95% CI: 1.48 to 6.13; p=0.001), and a maximum training walking speed of 0.2 m/s or more (MD=4.66; 95% CI: 0.37 to 9.70; p=0.03). For walking function, optimal interventions were also a disease duration of 3-6 months (gait speed: SMD=0.59; 95% CI: 0.15 to 1.03; p=0.008; step length: SMD=0.27; 95% CI: 0.06 to 0.56; p=0.04), an intervention time of 4-8 weeks (gait speed: SMD=1.01; 95% CI: 0.44 to 1.59; p=0.0006; step length: SMD=0.83; 95% CI: 0.54 to 1.12; p<0.00001), a maximum body weight support level above 30% (gait speed: SMD=0.79; 95% CI: 0.36 to 1.22; p=0.0003; step length: SMD=0.79; 95% CI: 0.47 to 1.11; p<0.00001), and a maximum training walking speed of 0.2 m/s or more (gait speed: SMD=1.26; 95% CI: 0.62 to 1.90; p=0.0001; step length: SMD=0.85; 95% CI: 0.38 to 1.31; p=0.0003). BWST demonstrates superior efficacy in enhancing balance and walking function compared to conventional rehabilitation, with an optimal intervention strategy including a disease duration of 3-6 months, an intervention period of 4-8 weeks, a maximum body weight support of 30% or more, and a maximum training walking speed of 0.2 m/s or greater.